Penerapan Perizinan Berusaha Berbasis Risiko Bagi Pelaku UMKM di Desa Cibatu kecamatan Cikarang Selatan Kabupaten Bekasi - Ida Farida; Muhammad Luthfi Radian (LPPM Universitas Ekasakti Padang, 2024)
Micro, Small and Medium Enterprises (MSMEs) are the most important pillar in the economic sector to dominate economic growth in Indonesia. Business legality is very necessary for MSMEs bisiness actors. The fact in the field is that there are still many business actors wh don’t have business legality. The Obstacles encountered include the lack of knowledge about business legality and the low education of MSMEs business actors. This has resulted in the inhibition of the development of MSMEs in Indonesia. In Government Regulation Number 7 of 2021 concerning the Ease of Protection and Empowerment of Cooperatives and MSMEs, it is stated that economic growth in Indonesia requires the empowernment and licensing of MSMEs. With the existence of the government regulation, the business license that has been designed in such a way by the Government to make it easier for business actors to issue their business legality. The legal issue that the author will examine is regarding the licensing of MSMEs that provide legal protection and realize a welfare state. MSMEs licensing as a form of legal protection is very important an has an impact, namely that the business license can be used for capital application with the aim of improving the MSMEs business for the better, being able to compete with other products in a larger market, getting assistance and empowerment from the Government so that it can realize a welfare state